67.5k views
1 vote
If h(x) = x – 7 and g(x) = x2, which expression is equivalent to (G ▪ H) (5)? (5 – 7)2 (5)2 – 7 (5)2(5 – 7) (5 – 7)x2

User Rost
by
5.8k points

2 Answers

5 votes

Answer:

A

Explanation:

User Ottis
by
5.0k points
4 votes

Answer:

The correct answer is (5 - 7)^2

Explanation:

To find this, start with the outermost equation g(x).

g(x) = x^2

Now put the next equation (h(x)) in for x in this equation.

(G ▪ H)(x) = (x - 7)^2

Now, put the number in for x in the equation given.

(G ▪ H)(x) = (5 - 7)^2

User GlassZee
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.